Cognitive–Cultural Balance in Designing Culture-Based HOTS Tasks: Evidence from Prospective Mathematics Teachers - Alifiani; Labuem, Susana; Suwanti, Vivi; Phadung, Muneeroh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to investigate how prospective mathematics teachers integrate cognitive and cultural dimensions in designing culture-based Higher Order Thinking Skills (HOTS) tasks. Using a qualitative descriptive approach, data were collected through task analysis, observation, and in-depth interviews. Data analysis in this study employed thematic analysis using a hybrid inductive–deductive approach. The study involved seventh-semester Mathematics Education students who had completed core pedagogical and professional courses as well as teaching practicum and were therefore considered ready as prospective teachers. Their task designs were analyzed using the Cognitive Demand and Cultural Value Framework, resulting in three classifications: cognitive dominance, cultural dominance, and cognitive–cultural balance, with one participant representing each category. Participants with cognitive dominance demonstrated strong mathematical reasoning and structured problem design but tended to disregard cultural authenticity and traditional norms. Conversely, culturally dominant participants displayed rich cultural sensitivity yet neglected mathematical coherence and contextual logic. Only participants achieving cognitive–cultural balance successfully integrated analytical rigor with cultural meaning, producing problems that were both mathematically valid and culturally grounded. These findings highlight that cognitive and cultural dimension are complementary rather than opposing forces. The study concludes that developing dual cognitive and cultural literacy is essential for prospective mathematics teachers to design transformative learning experiences that connect logical reasoning with cultural understanding, underscoring the need for teacher education institutions (LPTK) to integrate this balance explicitly into curriculum design to better prepare future teachers.